Optimisation topologique de surfaces additionnelles de tôles embouties - Ben-Elechi, Slim; Naceur, Hakim (European Journal of Computational Mechanics, 2006)
In this paper we present a new numerical approach for topologic optimization of additional surfaces (called addendum surfaces) which play an important role upon the quality of the final workpiece. This new approach is based on the coupling between an inverse approach used for the deep drawing simulation and an evolutionary algorithm. The results concerning shape optimization of additional surfaces of the square cup (Benchmark of Numisheet’93) and the Twingo dashpot cup show the efficiency and the industrial interest of the proposed approach.